2002
DOI: 10.1086/339480
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimization of Broadband Photometry for Galaxy Evolution Studies

Abstract: We have derived the uncertainties to be expected in the derivation of galaxy physical properties (star formation history, age, metallicity, reddening) when comparing broad-band photometry to the predictions of evolutionary synthesis models. We have obtained synthetic colors for a large sample (∼9000) of artificial galaxies assuming different star formation histories, ages, metallicities, reddening values, and redshifts. The colors derived have been perturbed by adopting different observing errors, and compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…These are key questions in galaxy evolution studies especially for the planning of galaxy surveys and observational proposals and for understanding the reliability of the results. In order to answer these questions we carry out a comprehensive test of various filter setups and their performance in recovering the galaxy physical properties (see also Gil de Paz & Madore 2002 for a similar study at low redshift using BC03‐type stellar population models). M06 discuss the importance of including the rest‐frame near‐IR in the fitting (illustrated in their fig.…”
Section: Spectral Energy Distribution Fittingmentioning
confidence: 99%
“…These are key questions in galaxy evolution studies especially for the planning of galaxy surveys and observational proposals and for understanding the reliability of the results. In order to answer these questions we carry out a comprehensive test of various filter setups and their performance in recovering the galaxy physical properties (see also Gil de Paz & Madore 2002 for a similar study at low redshift using BC03‐type stellar population models). M06 discuss the importance of including the rest‐frame near‐IR in the fitting (illustrated in their fig.…”
Section: Spectral Energy Distribution Fittingmentioning
confidence: 99%
“…The solutions, however, are still degenerate since various combinations of , E(BϪV ) ranging from 0 to 0.5 mag, and extinction laws (LMC, SMC, and C94) all produce a low residual fit to the data. Since the timescales for the burst and underlying components in the models are now fixed, we find that the dominant source of degeneracy is the age-extinction degeneracy (Gil de Paz & Madore 2002). This is in the sense that an older burst with less dust extinction may yield as good a fit to the data as a younger but more extincted burst.…”
Section: Stellar Mass Estimatesmentioning
confidence: 90%
“…The blue end corresponds to a rest frame of ∼0.18 mm and of ∼0.23 mm, respectively. Gil de Paz & Madore (2002) have shown that this filter combination is well suited for deriving physical properties of galaxies at from broadband z ∼ 0.7 data alone, including the star formation timescale, age, metallicity, and stellar mass.…”
Section: Stellar Mass Estimatesmentioning
confidence: 99%
“…In spite of the wealth of optical spectroscopic information currently available thanks to recent large-area surveys (mainly the 2dFGRS and the SDSS), SEDs still provide invaluable and complementary information. It is well known (e.g., Thuan 1985;Gil de Paz & Madore 2002) that for nearby galaxies NIR photometry can sensitively constrain the age, metallicity, and mass of stellar populations -but the situation is more complex in the case of strongly star-forming galaxies (see Noeske et al 2003). Alternatively, UV data provide information on the amounts of dust, the age and mass, and the star formation rate of galaxies on a broader time scale than traced by Hα emission.…”
Section: Imaging and Spectroscopic Datamentioning
confidence: 99%
“…Furthermore, it has been shown that the UV emission provides reliable SFRs for galaxies with weak or non-existing Hα emission, and that the latter increasingly underpredicts the FUV-derived SFRs for low-mass galaxies (Lee et al 2009a). Additionally, for a fixed number of photometric points, wider wavelength baselines can significantly reduce the uncertainties in the derived parameters (Gil de Paz & Madore 2002). Finally, the analysis of SEDs is not restricted to objects with SDSS spectra, and thus allows for a direct comparison with dwarfs at higher redshifts, where spectroscopic data are scarce, but multiwavelength imaging is abundant.…”
Section: Imaging and Spectroscopic Datamentioning
confidence: 99%